FUNGSIONALISASI UNDANG-UNDANG NOMOR 1 / PNPS TAHUN 1965 DAN PASAL 156a KUHP TERHADAP TINDAK PIDANA PENISTAAN AGAMA DI INDONESIA - IKHSAN '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Criminal acts of defamation of religion stipulated in Article 156 and 156a of the Criminal Code, which criminalize whoever intentionally publicly issued a feeling or does something which is fundamentally hostility, abuse or desecration of a religion followed in Indonesia with the intention that that person no religion anything that Belief in God Almighty.Criminal acts of defamation of religion provided for in Article 156 of the Criminal Code, is one of the "haatzaai-artikelen" formulated by crime controversial, which issued a statement feelings of hostility, hatred or demeaning to the object of the crime is, is the segment of the population, followed by an authentic interpretation.The purpose of this study How functionalizing Law No 1 / the 1965 and Article 156a of the Criminal Code Against Crime Blasphemy in Indonesia and Is Application of Law No. 1 / the 1965 and Article 156a of the Criminal CodeEffective in Addressing the follow-Blasphemy in Indonesia, From this study it can be concluded that the issuance of Law No. 1 / the 1965 in the handling of cases of religious defamation in Indonesia as a whole can not be received and run by all classes.Keywords: functionalizing, Law, Crime, Blasphemy